Outbreaks of sarcoptic mange in free‐ranging koala populations in Victoria and South Australia: a case series. Issue 7 (July 2017) - Speight, KN; Whiteley, PL; Woolford, L; Duignan, PJ; Bacci, B; Lathe, S; Boardman, W; Scheelings, TF; Funnell, O; Underwood, G; Stevenson, MA
Abstract : Objective: To describe outbreaks of sarcoptic mange caused by Sarcoptes scabiei in free‐ranging koalas in Victoria (December 2008 to November 2015) and South Australia (October 2011 to September 2014). Methods: Koalas affected by mange‐like lesions were reported by wildlife carers, veterinary practitioners or State Government personnel to the Faculty of Veterinary and Agricultural Sciences at The University of Melbourne and the School of Animal and Veterinary Sciences at The University of Adelaide. Skin scrapings were taken from live and dead koalas and S. scabiei mites were identified. Tissues from necropsied koalas were examined histologically. Results: Outbreaks of sarcoptic mange were found to occur in koalas from both Victoria (n = 29) and South Australia (n = 29) for the first time. The gross pathological and histopathological changes are described. Conclusion: We present the first reported cases of sarcoptic mange outbreaks in free‐ranging koalas.